Alcoholysis of Al2(OtBu)6 – Synthesis and Crystal Structure of Al9O3(OEt)21. Issue 1 (24th November 2017) - Nachtigall, Olaf; Hirsch, Tobias; Spandl, Johann
Abstract : When Al2 (O t Bu)6 is treated with ethanol, Al9 O3 (OEt)21 (1 ) is obtained, which is a missing link in the series of polynuclear aluminum alkoxides. Alcoholysis of Al2 (O t Bu)6 in 2‐propanol yields the well‐known homoleptic compound Al4 (O i Pr)12 (2 ). As recently published, similar reactions with Fe2 (O t Bu)6 gave different structures. However, there are recurring structural patterns from alkoxide chemistry found. For a deeper understanding of this hardly predictable chemistry, compounds have to be correlated by such common structural motifs. We briefly report the syntheses of1 and2 and the crystal structure of1 . In addition, we provide an improved synthetic procedure for the preparation of the precursor Al2 (O t Bu)6 . The structure of the new compound1 is comprehensively compared to related structures from literature. Abstract :